The changing English language psycholinguistic perspectives - Hundt, Marianne; Mollin, Sandra; Pfenninger, Simone E. (Cambridge Cambridge University Press, 2017)
"Easily accessible, the book features chapters by psycholinguists presenting cutting edge research on core factors and processes, and develops a model of how this may be involved in language change. Each chapter is complemented with one or several case study in the history of the English language in which the psycholinguistic factor in question may be argued to have played a decisive role. Thus, for the first time, a single volume provides a platform for an integrated exchange between psycholinguistics and historical linguistics on the question of how language changes over time"--Provided by publisher.
Part I. Frequency -- 2. The Ecclesiastes principle in language change / Harald Baayen, Fabian Tomaschek, Susanne Gahl and Michael Ramscar -- 3. Frequencies in diachronic corpora and knowledge of language / Martin Hilpert -- Part II. Salience -- 4. Salience in language usage, learning, and change / Nick C. Ellis -- 5. Low salience as an enabling factor in morphosyntactic change / Elizabeth C. Traugott -- Part III. Chunking -- 6. Chunking in language usage, learning, and change: I don't know / Nick C. Ellis -- 7. Chunking and changes in compositionality in context / Joan L. Bybee and Carol Lynn Moder -- Part IV. Priming -- 8. Priming and language change / Martin J. Pickering and Simon Garrod -- 9. From priming and processing to frequency effects and grammaticalisation? Contracted semi-modals in present-day English / Christian Mair -- Part V. Analogy -- 10. The role of analogy in language processing and acquisition / Heike Behrens -- 11. The role of analogy in language change: supporting constructions / Hendrik de Smet and Olga Fischer -- Part VI. Ambiguity -- 12. Syntactic ambiguity in real-time language processing and diachronic change / Claudia Felser -- 13. Ambiguity and vagueness in historical change David Denison -- Part VII. Acquisition and Transmission -- 14. Developing language from usage: explaining errors / Elena V. M. Lieven -- 15. Transferring insights from child language acquisition to diachronic change (and vice versa) / Maria Jose Lopez-Cous.
Includes bibliographical references and index.
Keywords: English language -- Psychological aspects; Psycholinguistics; English language -- History